Shaping A Student Self Efficacy Academic Through Live Modeling Technique (A Synthesis of Observational Learning in Social Cognitive Theory) - Hidayat, Ryan; Ramli, M (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2018)
In the perspective of social cognitive theory, humans as an actor that has a cognitive capability to observe, learn, understand, motivate, plan, act and evaluate an achievement or result that has been done. This perspective argues that a human can learn just by observation, although they do not have direct experience to do such specific tasks. This argument has revised a concept of behavioristic about imitation learning Miller and Dollard. Bandura has a viewpoint to have this result in his research with a triadic reciprocal determinism. Peoples has a cognitive function to observe and consideration to make a decision to act in their life circumstance not only reaction form their environment but their also an actor to make their self a decision-maker. So in a learning process, observational learning formed in live modeling. This modeling has an effect of influencing a mindset of the student in their self-belief, such competencies, capabilities to accomplish a task this self-belief known as self-efficacy. In self-efficacy has one source that links with an observational learning process, there is a vicarious experience. This article will describe and discuss a synthesis about live modeling in observational learning, linkage with vicarious experience in self-efficacy, and how to live modeling to shape a student's self-efficacy and a stage in the group counseling process.